Combining means of transport as a users' strategy to optimize traveling in an urban context: empirical results on intermodal travel behavior from a survey in Berlin. (July 2018) - Oostendorp, Rebekka; Gebhardt, Laura
Abstract: Intermodal travel behavior is becoming increasingly important, particularly in large cities. Using and combining different transport modes flexibly on a single trip is discussed as being crucial to a more efficient and sustainable urban transport system. However, research on intermodality has mainly addressed long-distance traffic or specific combinations. This study analyzes how intermodality is practiced in everyday mobility by looking at relevant mode combinations, trip purposes, spatial differentiation and the requirements of intermodal users. The article presents results on intermodal travel behavior from a survey conducted in different neighborhoods in Berlin in 2016 (n = 1098). The results show that many people use intermodal combinations in their everyday mobility. Intermodal travel behavior is significantly characterized by public transport modes and trips to work. Spatial differences in intermodal use become obvious with combinations of bike and public transport being strong in urban neighborhoods, car and public transport in decentralized neighborhoods and combinations of different means of public transport in well-connected neighborhoods. In addition, the study emphasizes that time efficiency is an important aspect for intermodal users, becoming apparent in the reasons they state for performing intermodal trips and their evaluation of interchanges. Intermodal travel behavior and users' needs must therefore be taken into account in urban planning if the aim is to make the most of intermodal combinations for an effective urban transport system. Highlights: Survey results on intermodal travel behavior in different neighborhoods in Berlin Intermodal combinations are used mainly on trips to work or for leisure activities. Public transport is the basis for most intermodal combinations. Combinations of public transport with bike or car show spatial differences Time-efficiency is important for intermodal use and the evaluation of interchanges.